2020
DOI: 10.3390/foods9081007
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics of Fermented Rice Using UHPLC Q-TOF MS/MS Reveals an Abundance of Potential Antihypertensive Compounds

Abstract: Enzyme treatment and fermentation of cereals are known processes that enhance the release of bound bioactive compounds to make them available for bioactivity. In this study, we tested the angiotensin converting enzyme (ACE) inhibitory ability of destarched rice, Prozyme 2000p treated destarched rice (DP), and fermented DP samples. Prozyme 2000p treatment increased the ACE inhibitory ability from 15 ± 5% to 45 ± 3%. Fermentation of the Prozyme 2000p treated samples with Enterococcus faecium EBD1 significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…The heatmap model’s color intensity was used to depict the relative abundance in the sample extract of Curculigo species, and its variation can tell us about the compounds diversity in the plant [ 29 ]. We used the peak area from the detected metabolites because it is widely accepted that the peak area of an analyte in a chromatogram is directly proportional to its concentration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heatmap model’s color intensity was used to depict the relative abundance in the sample extract of Curculigo species, and its variation can tell us about the compounds diversity in the plant [ 29 ]. We used the peak area from the detected metabolites because it is widely accepted that the peak area of an analyte in a chromatogram is directly proportional to its concentration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLS, as a supervised pattern recognition method, is often used to correlate medicinal plants’ biological activities with chromatographic or spectroscopic data (peak area or peak and absorbance value) [ 15 , 30 , 37 ]. The parameters used to create the PLS model are latent variables (LV), and its full cross-validation was applied for data validation and avoiding overfitting [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABTS activity was measured as described by Ofosu et al (2020) [21] with some modification. ABTS radical cation reagent was formed by the reaction of 7 mmol/L ABTS stock solution with 2.45 mmol/L potassium persulfate stock solution (1:1, v/v).…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%
“…Besides, there are other processes such as enzyme treatment and fermentation of cereals that enhance the release of bound bioactive compounds and make them available for bioactivity. Authors of [ 4 ] found that enzyme-treated destarched rice samples with subsequent fermentation contained known antihypertensive phenolic compounds and peptides that make these samples a promising material for developing cheap antihypertensive foods.…”
mentioning
confidence: 99%